2020 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2020
DOI: 10.1109/cvprw50498.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and detection from organised 3D point clouds: a case study in broccoli head detection

Abstract: Autonomous harvesting is becoming an important challenge and necessity in agriculture, because of the lack of labour and the growth of population needing to be fed. Perception is a key aspect of autonomous harvesting and is very challenging due to difficult lighting conditions, limited sensing technologies, occlusions, plant growth, etc. 3D vision approaches can bring several benefits addressing the aforementioned challenges such as localisation, size estimation, occlusion handling and shape analysis. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Future work should also explore alternative network architectures. Instead of using PointNet++, we are interested in one promising architecture, presented in the context of in-field broccoli head detection [9]. The authors take advantage of the fact that, as a result of the data acquisition technique, point clouds produced by some RGB-D sensors provide an organised structure and allow for the use of a CNN without need for projection.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should also explore alternative network architectures. Instead of using PointNet++, we are interested in one promising architecture, presented in the context of in-field broccoli head detection [9]. The authors take advantage of the fact that, as a result of the data acquisition technique, point clouds produced by some RGB-D sensors provide an organised structure and allow for the use of a CNN without need for projection.…”
Section: Discussionmentioning
confidence: 99%
“…It requires learning from a dataset of manually labeled plant skeletons. Le Louedec et al [41] detects broccoli heads in point cloud data. However, they require the cloud data to be organized in an image-like grid which limits their use cases to only RGB-D sensors that capture the scene from a single point of view.…”
Section: Plos Onementioning
confidence: 99%
“…In previous work, we have demonstrated the suitability of using the standard CNN architectures in 3D crop detection systems for robotic harvesters Le Louedec et al (2020b) using points and surface normals, reducing the network size and using directly shape and spatial information easily computed without learning. Such idea can be found in Rabbani et al (2006), where local surface normals and curvature combined with points connectivity allows segmentation of point cloud parts.…”
Section: Deep Learning For 3d Informationmentioning
confidence: 99%
“…A pure 3D crop detection system was proposed in Kusumam et al (2017a) for real-time detection of broccoli in the field which relied on hand-crafted features and SVM classifier. The suitability of using CNN architectures for the same application was later investigated in Le Louedec et al (2020b) with the superior results reported.…”
Section: D Vision and Shape Analysis In Agriculturementioning
confidence: 99%